Welfare and the employment issues related to foreign workers in Sabah: a case study of Mensuli estate / NurAziemah Jasni and Nasuddin Othman. - Jasni, NurAziemah; Othman, Nasuddin (Universiti Teknologi Mara Selangor, 2016)
The study analysed the welfare and employment issues related to foreign workers in Sabah. This study aims to determine the main factors that contribute to the oil palm productivity in relation to minimum wage, welfare management, and training provided to the foreign workers, to examine productivity status of the foreign harvesters and loose fruit collectors with welfare management and to examine the foreign harvesters’ and loose fruit collectors’ employment situations in oil palm plantations in Mensuli Estate. The method that had been used to obtain the data in this study was questionnaires distribution method and personal interviews. The questionnaires consisted of four (4) sections the questionnaire format based on Likert Scale. The data was analysed by using factorial analysis. The factor analysis identified seven factors that led to welfare and employment issues of foreign workers. The factors including competition with Indonesian palm oil plantation, training provided by the company, welfare management, satisfaction with the company welfare management, wage satisfaction, minimum wage and high cost of living. It was found that most of the respondents knew about the wage hike in Indonesia palm oil plantations and they were willing to return back to their homeland. Therefore the government should take an action to prevent the workers shortage issues in the plantation by encouraging local younger generation to work in the plantation sectors.